DINAMIKA HARIAN PEMILIHAN RUTE DAERAH KOPO DAN SEKITARNYA PADA PAGI HARI - Sulaksono Wibowo, Sony
Abstract : The objectives of this research were to study a day-to-day route choice making behaviour of households at Kopo Pemai and Margahayu residential areas in the southern part of Bandung. There are two main alternative routes heading to the city centre from the two residential areas i.e. Cibaduyut and Kopo routes. Route choice surveys were conducted using registration plate matching survey and home interview. Route choice observation by simulation was also conducted. Results from registration plate matching analysis at Kopo Permai found that the route choice splits on Cibaduyut and Kopo routes were 83.1% and 16.8%, and 61.8% and 38.2% for the same route choice splits at Margahayu. As route switching behavior is concerned, the highest switching rate of 2.7% was found at Kopo Permai and 3.8% at Margahayu. The coefficient of variation of travel times were found 0.33 and 0.12 for Cibaduyut and Kopo route at Kopo Permai and 0.17 for both of routes at Margahayu. From home interview at Kopo Permai, faster route was the most frequently stated as the reason for choosing route, followed by shorter route and habitual choice. Results from simulation experiment using artificial network found that route choice behaviour for informed traveler tend to be fluctuative between days. Attempts to mimick the route choice observation was also conducted using a simulation experiment. Given the limitation of the existing simulator, the results show that the route splits from simulation differ significantly from the observed route choice split. This partly because some of physical and empirical conditions could not be accomodated completely in the simulator. From simulation experiment at Kopo Permai it was found that route choice split on Cibaduyut and Kopo route was 0.38:0.62, whereas 0.33:0.67 in steady state user equlibrium (UE) condition. Moreover, from simulation experiment at Margahayu the route choice split was 0.81:0.19 and 0.87:0.13 in UE condition. In contrast to the traditional steady state method, using day to day simulation we can obtain a day to day evolution of route choice and distribution of the network performance.